The role of foreign capital in transformation of the polish economy - Siemiątkowski, Piotr (Torun International Studies, 2011)
The article shows the role of foreign capital in the transformation of the Polish economy after 1989. The new, democratic government collided with a number of problems. One of them was a huge shortage of capital. This gap was filled in by foreign investors. This paper presents both size of capital that flowed to Poland and the key directions of impact on the economy reform.